Biallelic loss of function of the promyelocytic leukaemia zinc finger (PLZF) gene causes severe skeletal defects and genital hypoplasia. Issue 11 (8th July 2008) - Fischer, S; Kohlhase, J; Böhm, D; Schweiger, B; Hoffmann, D; Heitmann, M; Horsthemke, B; Wieczorek, D
Abstract : Background: Deletions of 11q23 are associated with mental retardation, craniofacial dysmorphism, microcephaly and short stature. We present a patient with similar clinical findings, in addition to absence of the thumbs, hypoplasia of the radii and ulnae, additional vertebrae and ribs, retarded bone age and genital hypoplasia. Methods: Genomic DNA from the patient was screened for chromosomal imbalances by array-based comparative genomic hybridisation. DNA sequence analyses and reporter gene assays were performed in order to identify candidate gene mutations. Results: The patient has an ∼8 Mbp de novo deletion on the paternal chromosome 11, which includes the promyelocytic leukaemia zinc-finger gene ( PLZF, ZBTB16 ; OMIM 176797). The maternal PLZF allele harbours a recessive missense mutation (c.1849A→G), which leads to the substitution of a highly conserved methionine by valine (p.Met617Val) within a zinc-finger motif. Taking into account specific alpha-helical propensities of Val and Met, this mutation is likely to destabilise the alpha helix of the zinc finger that forms the contact with the DNA duplex, thus affecting the biological function as shown by reporter-gene assays. Discussion: The PLZF gene is one of five partners fused to the retinoic acid receptor α in acute promyelocytic leukaemia. We describe the first patient, to our knowledge, with a germline mutation of PLZF . Our findings as well as observations in Plzf -deficient mice indicate that PLZF is a key regulator of skeletal and male germline development. Furthermore, this case highlights the importance of searching for a recessive mutation on the non-deleted chromosome in patients with a microdeletion and atypical clinical findings.